Revealing the Ecstasy of Communication upon using Tik Tok: A Virtual Ethnography in Palopo City, Indonesia - Wahyuni Husain; Saifur Rahman; Intan Soliha Ibrahim; Achmad Sulfikar (Faculty of Social Sciences and Humanities Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2025)
This research uses virtual ethnography to analyze TikTok usage patterns and the phenomenon of communication ecstasy among students in Palopo City. The qualitative field research method employed involves the use of questionnaires, interviews, observation, and documentation. A total of 53 students from universities in Palopo City participated in the questionnaire, and four were selected for further analysis through interviews. Data were analyzed using reduction techniques, presentation, and drawing conclusions. The results reveal that TikTok usage is prevalent among students, with daily use averaging over three hours per day. The purpose of use varies, including entertainment, information seeking, stress relief, hobby expression, and money-making. The phenomenon of communication ecstasy is evident in students' addiction to digital symbols like